Review of research on agricultural vehicle autonomous guidance - Li, Ming; Imou, Kenji; Wakabayashi, Katsuhiro; Yokoyama, Shinya (International Journal of Agricultural and Biological Engineering, 2009)
A brief review of research in agricultural vehicle guidance technologies is presented. The authors propose the conceptual framework of an agricultural vehicle autonomous guidance system, and then analyze its device characteristics. This paper introduces navigation sensors, computational methods, navigation planners and steering controllers. Sensors include global positioning systems (GPS), machine vision, dead-reckoning sensors, laser-based sensors, inertial sensors and geomagnetic direction sensors. Computational methods for sensor information are used to extract features and fuse data. Planners generate movement information to supply control algorithms. Actuators transform guidance information into changes in position and direction. A number of prototype guidance systems have been developed but have not yet proceeded to commercialization. GPS and machine vision fused together or one fused with another auxiliary technology is becoming the trend development for agricultural vehicle guidance systems. Application of new popular robotic technologies will augment the realization of agricultural vehicle automation in the future. Keywords: agricultural vehicle, guidance, machine vision, GPS DOI: 10.3965/j.issn.1934-6344.2009.03.001-016 Citation: Ming Li, Kenji Imou, Katsuhiro Wakabayashi, Shinya Yokoyama. Review of research on agricultural vehicle autonomous guidance. Int J Agric & Biol Eng, 2009; 2(3): 1